The first prototype of spot-scanning proton arc treatment delivery. (August 2019) - Li, Xiaoqiang; Liu, Gang; Janssens, Guillaume; De Wilde, Olivier; Bossier, Vincent; Lerot, Xavier; Pouppez, Antoine; Yan, Di; Stevens, Craig; Kabolizadeh, Peyman; Ding, Xuanfeng
Highlights: First prototype of spot-scanning arc treatment (SPArc) delivery was performed on a clinical proton beam therapy machine. The measurements and simulation results demonstrate the feasibility and accuracy of this novel treatment modality. Proton arc therapy has the potential to improve the treatment delivery efficiency and simplify the treatment workflow. Abstract: Purpose: We report the first prototype of spot-scanning arc treatment (SPArc) delivery on a clinical proton beam therapy machine and evaluate its delivery accuracy and efficiency. Methods and materials: A new module called Proton Dynamic Arc Delivery (PDAD) was developed to allow simultaneously delivering spot-scanning proton beam treatments while rotating the gantry on an IBA Proteus®One proton machine. A series of measurements was performed to validate the basic beam characteristics. Subsequently, patient specific quality assurance (QA) of a brain SPArc plan was performed. Total SPArc treatment delivery time was also recorded and compared to the clinically delivered intensity modulated proton therapy (IMPT) treatment time. Finally, the log file of the SPArc plan was analyzed and processed to reconstruct the actual delivered dose. Results: All the basic beam characteristics were confirmed in the PDAD mode, similar as those measured using fixed gantry deliveries in clinical mode. The brain SPArc plan with similar or superior plan quality was delivered in 4 mins compared to total 11 mins for the clinical treatment of the three-field IMPT plan. The patient QA result showed a good agreement between the measured and calculated dose distributions with the gamma index of 98.6% (3%/3 mm). The analysis of the log file confirmed the accuracy of the SPArc plan delivery, with the gamma index of 98.3% (1%/1 mm) between reconstructed and the planned doses. Conclusion: The first prototype of dynamic proton arc delivery on a clinical proton therapy system was successfully performed. The measurements and simulations demonstrated the feasibility of SPArc treatment within the clinical requirements.